2017
DOI: 10.1016/j.molcel.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH2 Hajdu-Cheney Mutations Escape SCFFBW7-Dependent Proteolysis to Promote Osteoporosis

Abstract: Summary Hajdu-Cheney syndrome (HCS), a rare autosomal disorder caused by heterozygous mutations in NOTCH2, is clinically characterized by acroosteolysis, severe osteoporosis, short stature, neurological symptoms, cardiovascular defects, and polycystic kidneys. Recent studies identified that aberrant NOTCH2 signaling and consequent osteoclast hyperactivity are closely associated with the bone-related disorder pathogenesis, but the exact molecular mechanisms remain unclear. Here, we demonstrate that sustained os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 49 publications
(81 reference statements)
2
17
0
3
Order By: Relevance
“…E) were reported all related to bone metabolism. These results reflect those of Fukushima (2017), who found that sustained osteoclast activity is largely due to accumulation of NOTCH2 carrying a truncated C terminus that escapes FBW7‐mediated ubiquitination and degradation. Salivary secretion may contribute to postmenopausal bone health.…”
Section: Discussionsupporting
confidence: 88%
“…E) were reported all related to bone metabolism. These results reflect those of Fukushima (2017), who found that sustained osteoclast activity is largely due to accumulation of NOTCH2 carrying a truncated C terminus that escapes FBW7‐mediated ubiquitination and degradation. Salivary secretion may contribute to postmenopausal bone health.…”
Section: Discussionsupporting
confidence: 88%
“…The PEST domain is recognized by the E3 ligase complex for ubiquitin-mediated degradation of NOTCH2. Therefore, the mutations result in the translation of a truncated NOTCH2 protein resistant to ubiquitin-dependent degradation and a gain-of-NOTCH2 function (23). To investigate the mechanisms responsible for HCS, we created a mouse model termed Notch2 tm1.1Ecan harboring a point mutation (6955C3 T) in exon 34 of Notch2 upstream of the PEST domain.…”
Section: Hajdu Cheney Syndrome (Hcs) Is Characterized By Craniofacialmentioning
confidence: 99%
“…There have been no reports showing a skeletal phenotype in hetero- or homozygous LysM-Cre KI mice in the absence of a floxed target gene. The CtsK-Cre KI and LysM-Cre KI lines were used for the etiological study of rare bone disorders such as Hajdu-Cheney syndrome and cherubism [60, 64]. These studies have shown that accumulation of NOTCH2 protein in osteoclasts and increased activation of SYK by accumulation of SH3BP2 protein in myeloid lineage cells are responsible for the bone phenotypes, respectively.…”
Section: Cre Transgenic Mice Used For Studies In Osteoclastsmentioning
confidence: 99%